السلطة العثمانية وعلاقتها بمنطقة الزواوة في عهد الإمارة - مخلوف فاطنة (جامعــــــــة محمـــــــــــد بــــــــــوضياف, 2025)
تعالج هذه المذكرة موضوع إمارة كوكو باعتبارها إحدى الكيانات السياسية المحلية التي نشأت في منطقة زواوة (القبائل) خلال العهد العثماني الممتد من القرن 10هـ/16م إلى غاية 13هـ/19م، حيث حاولنا من خلالها تسليط الضوء على نشأة الإمارة وتطورها، والعوامل التي ساهمت في بروزها كقوة محلية متميزة ذات تنظيم سياسي وعسكري خاص بها، بالإضافة إلى دراسة علاقتها بالسلطة العثمانية في الجزائر. وتندرج تحت هذا الموضوع الإشكالية التالية: ما طبيعة العلاقة بين إمارة كوكو والسلطة العثمانية في الجزائر؟ وهل يمكن اعتبارها قوة مستقلة أم تابعة؟ وبالتالي، فإن هذه المذكرة تُعالج فترة حساسة من تاريخ الجزائر العثمانية عامة، والتاريخ المحلي لمنطقة القبائل خاصة، بهدف إبراز خصوصية الكيانات السياسية المحلية، وطرق إدارتها للسلطة، وآليات تفاعلها مع الحكم العث This thesisaddresses the topic of the Kingdom of Koukou, one of the local politicalentitiesthatemerged in the region of Zwawa (Kabylia) during the Ottoman period, spanningfrom the 10th AH / 16th CE century to the 13th AH / 19th CE century. It aims to shed light on the emergence and development of thisemirate, the factorsbehinditsrise as a prominent local power with a distinct political and military structure, and itsrelationshipwith the Ottoman authority in Algeria. This topic fallsunder the following central question: What was the nature of the relationshipbetween the Kingdom of Koukou and the Ottoman authority in Algeria? Can itbeconsidered an independent power or a subordinateone? Accordingly, thisthesis explores a crucial period in the generalhistory of Ottoman Algeria and the local history of the Kabyliaregion in particular. Itsaimis to highlight the uniqueness of local politicalentities, theirmethods of governance, and how theyinteractedwith the Ottoman state—contributing to a deeperunderstanding of the structure of authority in Algeria duringthatera.